EFFECTS OF IMMUNE MODULATORS ON GROWTH AND ECONOMIC PERFORMANCE OF BROILER CHICKENS - I. S. Sheikh; T. M. Asmat1; M. A. Bajwa; M. Z. Mustafa; N. Rashid; M. Rafeeq; M. M. T. Kiani; H. M. Ali; A. Raziq (Journal of Animal and Plant Sciences, 2020)
Immune modulators have been found beneficial for growth performance, physiological status, and immune function in broilers. Imbalance between pro-oxidants and anti-oxidants creates oxidative stress in fast growing broiler birds. Immune modulators are capable of reducing oxidative stress produced by excess production of ROS/RNS in rapidly growing body. The current project was designed to study the effects of supplementing different immune modulators on growth performance indices in broiler chicken in 3 separate experiments (n=240 chicks in each experiment). Immune modulators viz. vitamin C (500mg/L), vitamin E (200mg/L), nucleotides mixture (100mg/L) and DNA extract (100mg/L) were provided through drinking water. In the experiment I, immune modulators were offered only from day 1 to 21. In experiment II, immune modulators were supplemented for complete rearing period i.e. from day 1 to 42; whereas in the experiment III, immune modulators were only provided from day 22 to 42. Supplementation of immunomodulators revealed significantly (P<0.05) higher live body weight gain and better feed conversion ratio as compared to control group. Over all nucleotides performed more efficiently compared to other used immunomodulators in all three experiments with better feed conversion ratio. It was thus concluded from the study that the provision of immune boosters in starter or finisher phase simultaneously improved production indices and economic performance of broiler chickens.
Keywords: growth performance; immune modulators; nucleotides; vitamin C; vitamin E